EXCLI Journal; 21:Doc818; ISSN 1611-2156 2022
DOI: 10.17179/excli2022-4976
|View full text |Cite
|
Sign up to set email alerts
|

The association of ACE1, ACE2, TMPRSS2, IFITM3 and VDR polymorphisms with COVID-19 severity: a systematic review and meta-analysis

Abstract: Genes involved in the regulation of viral recognition and its entry into a host cell have been identified as candidates for genetic association studies on COVID-19 severity. Published findings on the effects of polymorphisms within ACE1 , ACE2 , TMPRSS2 , IFITM3 and VDR genes remained inconclusive, so we conducted a systematic review and meta-analysis in order to elucidate their potential involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 59 publications
3
15
0
Order By: Relevance
“…The genotype distributions deviated from that expected based on the Hardy–Weinberg equilibrium ( p < 0.01) which has been also extensively found in previous studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Overall, no significant differences in long-COVID symptoms were observed depending on the genotypes of any SNP: ACE2 rs2285666 ( Table 2 ), ACE2 rs2074192 ( Table 3 ), TMPRSS2 rs12329760 ( Table 4 ), TMPRSS2 rs2070788 ( Table 5 ).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…The genotype distributions deviated from that expected based on the Hardy–Weinberg equilibrium ( p < 0.01) which has been also extensively found in previous studies [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Overall, no significant differences in long-COVID symptoms were observed depending on the genotypes of any SNP: ACE2 rs2285666 ( Table 2 ), ACE2 rs2074192 ( Table 3 ), TMPRSS2 rs12329760 ( Table 4 ), TMPRSS2 rs2070788 ( Table 5 ).…”
Section: Resultssupporting
confidence: 81%
“…Some studies have correlated the T (A) allele of the ACE2 rs2285666 [ 4 ] and of TMPRSS2 rs12329760 [ 5 ] SNPs with lower severity of COVID-19 in an Indian population. These data have been also replicated in a multicountry study [ 6 ] and confirmed by the meta-analysis by Dobrijevic et al concluding that T alleles of ACE2 rs2285666 (OR 0.512, 95% CI 0.331–0.793) and TMPRSS2 rs12329760 (OR 0.734, 95% CI 0.560–0.960) SNPs were associated with lower risk of developing severe COVID-19 [ 7 ]. Another meta-analysis has found that TMPRSS2 rs12329760 was not associated with more severe COVID-19 manifestations, whereas ACE2 rs2285666 and ACE2 rs2074192 SNPs were associated with more severe COVID-19 manifestations by genotype but not by allele [ 8 ].…”
Section: Introductionsupporting
confidence: 53%
See 3 more Smart Citations